A CASE OF PLACENTA ACCRETA WITH THE FORMATION OF A LARGE UTERINE HERNIA OF THE POSTERIOR WALL OF THE UTERUS - Tskhay, Vitaly Borisovich; Domracheva, Marina Yakovlevna; Domracheva, Olga Alexandrovna (Mother and Baby in Kuzbass, 2026)
Placenta accreta (PAC) disorders occur when a mature placenta grows within a uterine scar. Although classically, placenta accreta with uterine hernia formation is mostly observed on the anterior wall of the uterus in the area of a cesarean section scar, in rare cases it can also develop in the posterior wall.The aim of this article is to report a case of placenta accreta with the formation of a large uterine hernia located on the posterior wall of the uterus.
Keywords: placenta previa; placenta accrete; uterine hernia; massive obstetric hemorrhage; hysterectomy